Classification of Management Models in the Field of Physical Culture and Sports - I. A. Abramyan (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
The article provides analysis of management models in the field of physical culture and sports, studies opinions and findings of works by different authors on this subject. Key features of management models in the field of physical culture and sports were highlighted and their differences were demonstrated. A new classification of management models in the field of physical culture and sports was put forward, it is based on analysis of world and home practices. The article gives characteristic of models, whose functioning takes place on the basis of the role of every key management entity in the field of physical culture and sports and interaction between state, public and private sectors. The classification also describes possible configurations in case of mixing of management models in the field of physical culture and sports. Key conditions of each model functioning and factors of their use in practice were depicted. Findings of the analysis can be used in practice to build management model in the field of physical culture and sports in the Russian Federation.